Water resources and the fishing industry of Kalmykia during the nep years - B. A. Erdneeva; Yu. S. Shurguchieva (Nomadic Civilization: Historical Research)
This article provides a brief analysis of the water resources of Kalmykia in relation to the history of the fishing industry in the region in the lower reaches of the Volga and mainly in the Caspian region. Aquatic biological resources, especially fish, play a significant social and economic role among all the natural resources of our country. In the modern period, the fishing industry still plays a huge role in the development of the national economy of the Russian Federation. The GDP of Russia and the GRP of the subjects of the Federation, food security of the country, social well-being of our citizens depend on how the Russian fishing industry will develop as a whole and in its regions, since fish products are an important and necessary component of healthy nutrition and human life. The purpose of the article is to show the complex process of the emergence and development of the fishing industry of the Kalmyk Autonomous Region using the example of Kalmykrybtrest in the 1920s. In the modern period of development of the country’s market economy, the study of the historical experience of the emergence and development of the fishing industry of Kalmykia in the context of the new economic policy is very relevant from the point of view of the organization of the fishing business and management methods. The use of historical and problemchronological methods in the work allowed us to highlight the history of the formation of the fishing industry of Kalmykia in the first decade of Soviet power, to show the features of its development. The article is based on various sources, mainly on archival materials and published works on the history of the fishing industry of the Kalmyk Autonomous Region. The focus of the study is the study and analysis of party and state decisions of the center, the Kalmyk Autonomous Region and the Astrakhan province in the 1920s, aimed at the territorial definition of fisheries and the search for optimal ways of developing the fishing industry of the steppe region. One of the timely and correct decisions of the federal and regional authorities was the organization in 1923 of the Kalmrybaktrest, whose activities are thoroughly discussed in this article.